Clinicopathological and Prognostic Role of Long Noncoding RNA Linc00152 in Various Human Neoplasms: Evidence from Meta-Analysis. (23rd November 2017) - Miao, Chenkui; Zhao, Kai; Zhu, Jundong; Liang, Chao; Xu, Aiming; Hua, Yibo; Zhang, Jianzhong; Liu, Shouyong; Tian, Ye; Zhang, Chao; Wang, Yuhao; Su, Shifeng; et al.
Abstract : Recent researches have demonstrated that long noncoding RNA linc00152 was aberrantly upregulated in multiple tumor types. High expression of linc00152 was associated with poor outcomes in cancer patients. Therefore, we conducted this meta-analysis to evaluate its potential value as a prognostic predictor in various human neoplasms. Eligible studies were searched through several electronic databases including PubMed, Embase, Web of Science, and the Cochrane Library. Eight original studies including 752 cancer patients were ultimately enrolled. Statistical analysis suggested that overexpression of linc00152 was significantly correlated with unfavorable overall survival (OS) (HR = 2.05, 95% CI: 1.59–2.64) and disease-free/progression-free survival (DFS/PFS) (HR = 3.52, 95% CI: 1.82–6.79) in cancer patients. In addition, a significant correlation was observed between aberrant linc000152 expression and lymph node metastasis (LNM) (OR = 2.49, 95% CI: 1.57–3.94) but not in vessel invasion (VI) (OR = 1.02, 95% CI: 0.54–1.93) and distant metastasis (DM) (OR = 0.600, 95% CI: 0.213–1.689). Our meta-analysis demonstrated that high linc00152 expression significantly predicted inferior OS and DFS/PFS in multiple neoplasms, as well as advanced LNM and VI. Linc00152 may serve as a potential indicator in predicting poor outcomes and metastases of diverse cancers.